THE KYAI’S POLICY IN DEVELOPING THE MADANIAH SYSTEM AT ISLAMIC BOARDING SCHOOL OF MANBAUL ULUM TANGSIL WETAN BONDOWOSO - Arifin, Zainul; Arbaiyah, Arbaiyah; Wahyuni, Titis Sri; Ayu, Sukma (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
This study examines the Kyai’s policy in developing the madaniah system at Islamic boarding school Manbaul Ulum Tangsil Wetan Bondowoso, revealing an intriguing phenomenon in which the Kyai, as the central figure, not only serves a spiritual role but also acts as a strategic policymaker in building a modern, participatory, and socially adaptive pesantren governance system. This reflects the transformation of the Kyai’s role in responding to contemporary challenges through a managerial approach grounded in Islamic values. This research employs a phenomenological qualitative approach, with data collected through in depth interviews with the Kyai, Islamic boarding school administrators, and students, participant observation of leadership and institutional activities, and documentation analysis of formal pesantren records. Data were analyzed using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing and verification to uncover deeper patterns and meanings of the policy practices. Data presentation was conducted narratively through thematic categorization and direct informant quotations, with validity ensured through method and source triangulation. This approach allows the researcher to capture the Kyai’s leadership reality holistically, deeply, and contextually within the framework of institutional transformation based on madaniah values. The result reveal that the Kyai, as the primary actor, plays a strategic role in formulating and implementing policies grounded in a transformative vision, local wisdom, and moderate Islamic values. The madaniah system is applied through organizational restructuring, administrative transparency, the integration of formal and informal education, and student empowerment via entrepreneurship and digital innovation. These policies not only strengthen the pesantren’s resilience in facing contemporary challenges but also enhance its social contribution in fostering a civil society. This study recommends the formulation of sustainable policies based on participation and collaboration among pesantren stakeholders to reinforce a competitive and Islamically rooted madaniah system.